2012
DOI: 10.7809/b-e.00078
|View full text |Cite
|
Sign up to set email alerts
|

The Tree Biodiversity Network (BIOTREE-NET): prospects for biodiversity research and conservation in the Neotropics

Abstract: Biodiversity research and conservation efforts in the tropics are hindered by the lack of knowledge of the assemblages found there, with many species undescribed or poorly known. Our initiative, the Tree Biodiversity Network (BIOTREE-NET), aims to address this problem by assembling georeferenced data from a wide range of sources, making these data easily accessible and easily queried, and promoting data sharing. The database (GIVD ID NA-00-002) currently comprises ca. 50,000 tree records of ca. 5,000 species (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…We compiled a list of 2793 target tree species from the BIOTREE‐NET forest plot database (Cayuela et al . ). The species names were standardized using The Plant List (http://www.theplantlist.org/) as a reference checklist.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…We compiled a list of 2793 target tree species from the BIOTREE‐NET forest plot database (Cayuela et al . ). The species names were standardized using The Plant List (http://www.theplantlist.org/) as a reference checklist.…”
Section: Methodsmentioning
confidence: 97%
“…For this, we generated 380 S‐SDMs based on the predicted ranges of 1224 tropical tree species in Mesoamerica by combining 19 SDM and ensemble methods with 20 threshold criteria using presence‐only data from the Global Biodiversity Information Facility (GBIF), and we compared the outcomes in species richness and composition with ground‐truth information provided by the BIOTREE‐NET forest plot database (Cayuela et al . ). Specifically, we aimed to answer the following question: Which combination of SDM algorithms (or ensemble method) and threshold criteria maximize the performance of S‐SDMs in terms of species richness and composition?…”
Section: Introductionmentioning
confidence: 97%
“…For these plots, incidence records were based on trees exceeding 5 cm in DBH. Data were obtained from the BIOTREE-NET website (Cayuela et al 2012a). As in the first case study, species (Cayuela et al 2012b).…”
Section: Description Of Case Studiesmentioning
confidence: 99%
“…As noted by Tundisi and Matsumura-Tundisi (2008), the Neotropics may contain the greatest number of plants and animals among all biogeographic regions. Anthropogenic disturbances, especially deforestation, urbanisation and climate change, threaten the integrity of the Neotropics and its biodiversity (Millenium Ecosystem Assessment 2005;Cayuela et al 2012). For example, Kehoe et al (2017) estimated that upwards of 30% of species richness and 31% of species abundance are at risk of loss in tropical areas due to intensification of agricultural stressors.…”
mentioning
confidence: 99%
“…For example, Kehoe et al (2017) estimated that upwards of 30% of species richness and 31% of species abundance are at risk of loss in tropical areas due to intensification of agricultural stressors. This is problematic because most Neotropical biodiversity, especially invertebrates, remains undescribed and undocumented, and some of it is at risk of extirpation and extinction (Contrador, Kennedy, and Rozzi 2012 Cayuela et al (2012) indicated that one of the main problems of conservation is the inadequate knowledge of descriptive taxonomy and the distribution of organisms, which is especially true for the Neotropics. Simple logic dictates that the more biodiversity is identified and described, the more likely conservation efforts aimed at protecting it will be successful.…”
mentioning
confidence: 99%